LEGAL POSITIVISM DALAM HUKUM ISLAM (Studi Kritis Terhadap Epistemologi Hukum Mazhab Hanbali) - Nur Aris (Jurnal Penelitian, 2017)
This study aims to understand the structure of logical system in the Hanbali School and trace the existence of the ideas of legal positivism in it. This study focusedon the Hanbali School of Jurisprudence, since it is often referred to as the textual-inclined Jurisprudence. The ideas of legal positivism are very close to textualism. The primary source of data in this research is the books of fiqh that related to the Hanbali school category. The data collection and the analysis technique were adopted from the content analysis method systematicallyto deeply describe the epistemological structure of the Hanbali School and the ideas of the legal posistivism in it.